الطاقة المتجددة في الجزائر كمدخل لتحقيق التنمية المستدامة - مسعودي, فاطمة الزهراء; جمعي, اسماء (جامعة الوادي University of Eloued, 2018)
تحتل الطاقة المتجددة أهمية بالغة من حيث إمكاناتها ومصادرها وكيفية استغلالها وتكاليف هذا الاستغلال وهو ما تفطنت له الدول بالبحث عن الطاقة البديلة للطاقة النابضة،والجزائر حالها كحال بقية الدول تتأثر بتحولات الاقتصاد العالمي خاصة التحولات في مجالات الطاقة لهذا أخذت المبادرة لخوض غمار التجربة في الاستثمار في الطاقة المتجددة كطاقة بديلة من اجل تحقيق التنمية المستدامة و حفظ حق الأجيال القادمة في الثروات الطبيعية لدولتهم من ناحية وتحفيز الاستثمارات التنموية من ناحية أخرى. وهوا ما نحاول إبرازه في هذه الورقة البحثية وذلك بتسليط الضوء على احد المشاريع الهامة في هذا المجال والمتمثل في مشروع تطبيق الطاقة الشمسية الفوتوفولطية في الجنوب الكبير . The renewable energy is very important in terms of its potential and sources, how it is exploited and the costs of this exploitation. This is what the countries have been looking for in alternative energy for the energy of the energy. "Algeria, like other countries, is affected by the changes in the world economy, especially the shifts in energy. This initiative took the initiative to invest in energy. Renewable energy as an alternative energy for achieving sustainable development and preserving the right of future generations to the natural wealth of their state on the one hand and to stimulate development investments on the other hand And what we are trying to highlight in this paper by highlighting one of the important projects in this area, which is the project of solar photovoltaic application in the South South.
مقال
Keywords: الطاقة، الطاقة المتجددة، الطاقة الشمسية، طاقة الرياح، التنمية المستدامة، الجزائر، البيئة.; Energy, Renewable energies, Solar energy, Wind energy, Sustainable development, Algeria, Environment.